Dualism of Public Relations Regulation (Legal and Regulatory Regulation) - V. F. Popondopoulo (Теоретическая и прикладная юриспруденция)
The article examines the issues of differentiation of the regulation of public relations, defined primarily by the differentiation of public relations, and then inherent in their legal forms (based on self-regulation) and external regulatory forms (based on power regulations). The need to renounce the traditional differentiation of the right to industry, including its division into so-called private and public law, is justified because it reflects external forms of expression of law, i.e. differentiation of legislation governing a variety of public relations, divided into private and public relations. The notion of dualism (pluralism) of the law must be replaced (or at least interpreted) with the notion of dualism of the regulation of public relations, meaning legal and regulatory regulation, with all the ensuing consequences. Such an approach implies the need to clarify the entire terminology range of jurisprudence. This article discusses issues such as the legal and regulatory regime (mechanism) of public relations regulation, legal and regulatory principles for regulating public relations, legal and regulatory legal facts, as circumstances that are the basis for the emergence, change and termination of legal relations and power relations.